2008
DOI: 10.1007/s11854-008-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

Overconvergent series of rational functions and universal Laurent series

Abstract: In this paper, series of rational functions with fixed poles, which have restricted growth near the poles are considered. If they converge with a geometric rate on a continuum, a phenomenon of overconvergence takes place, in the sense that the convergence extends to a certain maximal domain. From this result, some properties of universal Laurent series are derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…In 2005, Bayart [44] established the dense-lineability in H(D) of the class of these functions f , which are known as universal Taylor series. Since 1996, many extensions of these results, for other domains and more restrictive classes of functions, have been performed (see the recent papers [30,49,53,132,228] and references therein). They can be put into a more general context.…”
Section: Hypercyclity and Dense-lineability An Extreme Case Of Lineamentioning
confidence: 99%
“…In 2005, Bayart [44] established the dense-lineability in H(D) of the class of these functions f , which are known as universal Taylor series. Since 1996, many extensions of these results, for other domains and more restrictive classes of functions, have been performed (see the recent papers [30,49,53,132,228] and references therein). They can be put into a more general context.…”
Section: Hypercyclity and Dense-lineability An Extreme Case Of Lineamentioning
confidence: 99%
“…This notion was introduced by Costakis, Nestoridis and Papadoperakis [5], who showed that the collection U L ( ; 1 ; :::; k ) of functions with this property is a dense G subset of H( ). Subsequent work on universal Laurent series includes [6], [12], [15], [16] and [20].…”
Section: Universal Laurent Seriesmentioning
confidence: 99%
“…Next, let K A j nf j g be a compact set with connected complement, and let g 2 C(K) \ H(K ). By Theorem 5 of [16] we can choose a sequence (N k ) in N such that…”
Section: Universal Laurent Seriesmentioning
confidence: 99%
“…Sthn perÐptwsh aut , to er¸thma sqetik me thn Ôparxh kajolik¸n seir¸n Taylor eÐnai pio polÔploko, kurÐwc epeid to sÔnolo twn poluwnÔmwn den eÐnai puknì ston antÐstoiqo q¸ro twn olìmorfwn sunart sewn. Gia èna mh apl sunektikì tìpo Ω, tou opoÐou to sumpl rwma perièqei mÐa mh fragmènh sunist¸sa , isqÔei ìti U(Ω, ξ) = ∅ gia kje epilog kèntrou ξ ∈ Ω (blèpe [54], [51] kai [34]). Apì thn llh pleur, arketoÐ sug-grafeÐc apèdeixan thn Ôparxh kajolik¸n seir¸n Taylor se exeidikeumènouc mh apl sunektikoÔc tìpouc (blèpe [73], [50], [24], [12], [29], [61], [5]).…”
Section: H Apìdeixh Thcunclassified
“…Apì thn llh pleur, arketoÐ sug-grafeÐc apèdeixan thn Ôparxh kajolik¸n seir¸n Taylor se exeidikeumènouc mh apl sunektikoÔc tìpouc (blèpe [73], [50], [24], [12], [29], [61], [5]). Ja jèlame na epishmnoume, ìti sthn perÐptwsh aut h klsh U(Ω, ξ) exarttai genik apì to ξ (koÐta [50]), prgma pou den isqÔei ìtan to Ω eÐnai apl sunektikì (koÐta [54]).…”
Section: H Apìdeixh Thcunclassified